Quantitative susceptibility mapping and 23Na imaging-based in vitro characterization of blood clotting kinetics - Schneider, Till M.; Nagel, Armin Michael; Zorn, Markus; Wetscherek, Andreas; Bendszus, Martin; Ladd, Mark E.; Straub, Sina (NMR in biomedicine, 2018)
Blood clotting is a fundamental biochemical process in post-hemorrhagic hemostasis. Although the varying appearance of coagulating blood in T1- and T2-weighted images is widely used to qualitatively determine bleeding age, the technique permits only a rough discrimination of coagulation stages, and it remains difficult to distinguish acute and chronic hemorrhagic stages because of low T1- and T2-weighted signal intensities in both instances. To investigate new biomedical parameters for magnetic resonance imaging-based characterization of blood clotting kinetics, sodium imaging and quantitative susceptibility mapping (QSM) were compared with conventional T1- and T2-weighted imaging, as well as with biochemical hemolysis parameters. For this purpose, a blood-filled spherical agar phantom was investigated daily for 14 days, as well as after 24 days at 7 T after initial preparation with fresh blood. T1- and T2-weighted sequences, a three-dimensional (3D) gradient echo sequence and a density-adapted 3D radial projection reconstruction pulse sequence for 23Na imaging were applied. For hemolysis estimations, free hemoglobin and free potassium concentrations were measured photometrically and with the direct ion-selective electrode method, respectively, in separate heparinized whole-blood samples along the same timeline. Initial mean susceptibility was low (0.154 ± 0.020 ppm) and increased steadily during the course of coagulation to reach up to 0.570 ± 0.165 ppm. The highest total sodium (NaT) values (1.02 ± 0.06 arbitrary units) in the clot were observed initially, dropped to 0.69 ± 0.13 arbitrary units after one day and increased again to initial values. Compartmentalized sodium (NaS) showed a similar signal evolution, and the NaS/NaT ratio steadily increased over clot evolution. QSM depicts clot evolution in vitro as a process associated with hemoglobin accumulation and transformation, and enables the differentiation of the acute and chronic coagulation stages. Sodium imaging visualizes clotting independent of susceptibility and seems to correspond to clot integrity. A combination of QSM and sodium imaging may enhance the characterization of hemorrhage.
Gesehen am 08.04.2020
Im Titel ist "23" in 23Na hochgestellt